2013
DOI: 10.17796/jcpd.37.3.d70710016518p58n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Periodontal Biofilm in Down Syndrome Patients: A Comparative Study

Abstract: The aim of this study was to characterize the main periodontal bacterial species in Down syndrome (DS) pa-tients with and without periodontitis. Method: This cross-sectional study involved 75 DS patients, 45 with and 30 without periodontitis. Informed consent, health and dental questionnaires and periodontitis diagnosis were performed. PCR and LAMP assays were performed on subgingival dental plaque sample. Results: Tannerella forsythia was the most frequent bacteria detected in the group with and without perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 28 publications
4
20
1
2
Order By: Relevance
“…nigrescens and T . forsythia ); these rates were higher than those reported in previous studies [ 2 , 5 , 6 , 12 , 13 ]. However, considering the number of bacterial cells of each species, children and adolescents with DS exhibited a higher percentage of microorganisms present in saliva compared to participants in the ND group.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…nigrescens and T . forsythia ); these rates were higher than those reported in previous studies [ 2 , 5 , 6 , 12 , 13 ]. However, considering the number of bacterial cells of each species, children and adolescents with DS exhibited a higher percentage of microorganisms present in saliva compared to participants in the ND group.…”
Section: Discussioncontrasting
confidence: 71%
“…The periodontal status results showed that the DS group had a significantly higher percentage of participants with periodontal inflammation, as estimated by the gingival bleeding index; the data were consistent with previous studies that revealed a susceptibility to disease among children and adolescents with Down syndrome [ 2 6 ]. The high prevalence and severity of gingival bleeding can be attributed to factors such as immunodeficiency [ 3 , 4 ], elevated and early colonization by periodontopathic bacteria [ 2 , 5 , 6 ] and motor difficulty in performing oral hygiene, with a subsequent accumulation of plaque [ 3 , 7 , 13 ]. However, the mean plaque index in the present study was low and was similar in both groups, thus corroborating previously reported data [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies involved dental service users (Alves et al 2016;Batista, Moreira, Rauen, Corso, & Fiates 2009;Finkelman, Stark, Tao, & Morgan 2014;Özgül et al 2014;Seirawan, Schneiderman, Greene, & Mulligan 2008;Zizzi et al 2014), and in four papers, a high prevalence of daily toothbrushing was reported (Fernandez, Descamps, Fabjanska, Kaschke, & Marks 2016;Hsieh, Murthy, Heller, Rimmer, & Yen 2018;Margaritis, Koletsi-Kounari, Mamai-Homata, & Kiriakou 2012;Seirawan et al 2008). Of the clinical studies assessing the more severe form of periodontal health (periodontitis), a significant level of disease was recorded, with the prevalence in adults with intellectual disabilities ranging from 22.5% to 69.2% (Alves et al 2016;Cheng, Leung, & Corbet 2008;Davies et al 2008;Finkelman et al 2014;Margaritis et al 2012;Martinez-Martinez et al 2013;Moosani et al 2014;Morgan et al 2012;Özgül et al 2014;Zizzi et al 2014).…”
Section: )mentioning
confidence: 99%
“…; Martinez‐Martinez et al . ), impaired immune response and increased gingival inflammation (Barr‐Agholme et al . ; Otsuka et al .…”
Section: Introductionmentioning
confidence: 99%